Enhancement of efficiency and mitigation of pollutan emissions in a compression ignition engine by the utilization of rice bran oil as green fuel - Norhafana, M.; Ihsan, C. K.; Noor, M. M.; Hairuddin, A. A.; Kadirgama, K.; Ramasamy, D.; Hussein, A. M. (Institute of Physics, 2024)
The current investigation involved the implementation of a research experiment aimed at assessing the operational and emission attributes of a compression ignition direct injection engine comprising a single cylinder. The engine was fuelled with rice bran oil (RBO), and its performance was analysed under different engine loads. The performance metrics that were analysed included the brake specific fuel consumption BSFC), brake thermal efficiency (BTE), exhaust gas temperature (EGT), and cylinder pressure. The exhaust emission parameters that were investigated include carbon monoxide (CO), carbon dioxide (CO2), hydrocarbons (HC), and oxide of nitrogen (NOX). The study compares the results obtained from an experimental investigation involving different variants of rice bran oil (RBO50, RBO75, RBO100) with those obtained from a diesel engine (RBO00). The lowest BSFC obtained for RBO100 is around 0.29 kg/kWh at maximum load conditions (75 %), while the highest obtained for RBO00 is 0.33 kg/kWh. For all operations of diesel and RBO blends, it was discovered experimentally that the BSFC increases until 25 % of engine load and then starts to decline as the engine load is raised. At normal engine load circumstances, RBO75 has the highest thermal efficiency, while RBO00 has the lowest. The high EGT reading of RBO50 blends was due to the high calorific value (CV) of the fuel blends, which produced more heat per unit mass than RBO75 and RBO100. RBO75 achieved the highest cylinder pressure under both half and full load scenarios. RBO00 (pure diesel) achieved the lowest cylinder pressure under both half and full load scenarios. RBO outscored diesel in terms of efficiency of engine. The exhaust emission characteristics that were assessed included NOX, CO2, HC, and CO. The experimental outcomes of the study using rice bran oil-based fuels, specifically RBO50, RBO75, and RBO100, are being contrasted with those of diesel fuel (RBO00). The findings indicate that emissions of CO, CO2, HC, and NOX are lower when using RBO75 and RBO100 compared to diesel fuel. Furthermore, an analysis was conducted to determine the HC emissions of both RBO75 and RBO100 fuels at two distinct engine speeds, specifically 3500 rpm and 2000 rpm. The HC emission level for RBO75 was observed to be at its peak of 211 ppm when the engine speed reached 3500 rpm. The RBO50 fuel exhibits lower levels of CO emissions, measuring at 1.2% (3500 rpm) and 0.32% (2000 rpm). Similarly, CO2 emissions are also reduced with RBO50, measuring at 8.3% (3500 rpm) and 6.9% (2000 rpm). These exhaust emission reductions are observed when comparing RBO50 to diesel (RBO00) and other fuel mixtures, under a 75% load condition. Elevated levels of NOX emissions were detected in diesel fuel (RBO00) at concentrations of 499 ppm (3500 rpm) and 599 ppm (2000 rpm). In comparison to other fuels such as RBO50, RBO75, and RBO100, these higher NOX emissions were noted. In summary, the emission properties of RBO were shown to be superior to those of diesel fuel. The optimal blend for emissions reduction, including CO2, CO, NOX, and HC, was determined to be RBO50.